The study of pig dna analysis methods in cosmetics: a review - Sofiyani, Ratu Amada; Hariyanti, Hariyanti; Rahmi, Hanifah (Journal of Halal Science and Research, 2021)
Collagen is one of the components used for cosmetics. Functionally, collagen is derived from pig fat, which functions as a skin conditioning agent (Emollient), emulsion stabilizer (Emulsifier), and as ingredient to increase the viscosity of cosmetic preparations. The method that can detect pig content is the PCR method, which can confirm the presence of DNA content in pigs. In this study, an analysis of cosmetic products containing porcine DNA was carried out using the PCR method. This research was divided into two stages: the initial stage was DNA extraction, and the second stage was PCR analysis. This research is a study through literature study using the narrative review technique. This study aimed to collect information and examine the analysis method of identifying pig DNA contained in cosmetics to obtain the right and accurate way through a literature approach. From the literature study results, it can be concluded that the best extraction method for the isolation of porcine DNA in cosmetic preparations is the extraction method with the Boom Method, while the DNA analysis used to identify porcine DNA in cosmetics is RT-PCR (Real-time Polymerase Chain Reaction). Conventional PCR is because both methods have their respective advantages. The RT-PCR (Real-time Polymerase Chain Reaction) method can amplify and quantify the number of target DNA molecules. The Conventional PCR Method can form DNA bands based on the amplification value.